Implementation of Management Information System Using Machine Learning Technology - Eddy Soeryanto Soegoto; Hayin Ananta; Ilham Zaki; Muhammad Ikhlas Naufalsyah Ranau (International Journal of Research and Applied Technology (INJURATECH), 2022)
Implementation of a management information system using Machine Learning technology with the aim of solving the problems owned by the shop owner, namely the owner has a problem in terms of increasing sales. Observation method as data collection by making direct observations of the object under study with the relevant agencies to collect data and information related to existing problems. Research on the implementation of information systems has succeeded in increasing sales by 1.5% each month, using Machine Learning technology, a product sales recommendation system. Because based on the existing problems required an information system to assist in increasing sales. Machine Learning technology used in this research is a product recommendation system that can affect sales increase.